The Big Three Perfectionism Scale–Short Form: An item response theory analysis of Italian workers - Svicher, Andrea; Gori, Alessio; Di Fabio, Annamaria (Frontiers in Psychology, 2022)
Background: The present study examined the psychometric properties of the Big Three Perfectionism Scale–Short Form (BTPS-SF) using Rasch and Mokken item response theory (IRT) analyses, which have not previously been applied to the BTPS-SF. Materials and Methods: A total of 401 Italian workers (Mage = 46.78; SD = 10.1; male = 48.9%; female = 51.1%) completed the BTPS-SF questionnaire. We conducted confirmatory factor analyses of the BTPS-SF and IRT analyses using the generalized partial credit model (GPCM) and Mokken scale analysis. Discrimination and difficulty parameters were calculated. The Loevinger coefficient of scalability was computed. Item characteristic curves (ICC), test information function (TIF), and differential item functioning (DIF) for gender were calculated. Results: A three-factor solution revealed the best fit. Thus, IRT analyses were performed for each BTPS-SF factor: rigid perfectionism (RP), self-critical perfectionism (SP), and narcissistic perfectionism (NP). All the items showed Loevinger coefficients from medium to strong and discrimination parameters from medium to very high. No DIF for gender was found. Conclusions: The Big BTPS-SF shows good psychometric properties for Italian workers. Future research is warranted to examine the findings in workers from different countries.